Enhancing Students’ Critical Thinking and Confidence through Indirect Explicit Grammar Instruction (IEGI) in Learning Grammar - Ulfatul Ma’rifah (Universitas Muhammadiyah Gresik, 2018)
The aim of this research is to find the strategy how Indirect Explicit Grammar Instruction(IEGI) is able to enhance students‟ critical thinking and confidence in learning tenses. Sincestudents usually tend to memorize the form of patter in learning tenses, as a result they havebeen repeated rule presentations of grammar structures and lose their sense of criticalthinking to discover. More over, learning grammar on isolated way also make students haveless confidence to speak because they can memorize the pattern, but they cannot use themaccurately. Using classroom action research in two cycle which every cycle consists of threemeetings, the data are collected by using observation cheklist, rubric, test, qestionnare andstudents participation sheet. The observation cheklist is used to get the data of theimplementation of IEGI during teaching learning activities in the classroom which studentswork in group. The result from rubric shows the improvement of students‟ ctitical thinkingability improve from 54.05% into 82.50%. While from the test which covered the ability inanalyzing and answering questions which need Higher Order Thinking improve significantlyfrom 47.56% into 80.90 %. While students‟ confidence improves significantly from 55.56%into 78.10%